Planting Hope, Securing Housing: TAPERA Communication Strategy at PT CJ Logistics Service Indonesia (Oratio Directa, 2025)
This qualitative case study examines how PT CJ Logistics Service Indonesia communicates the People's Housing Savings policy (TAPERA). Interviews, field observation, and documents provide evidence from HR officers Adimas Anggara and Michael Aditya and employees Ade Dwi Prasetyo, Gunawan, Bambang Prihatin, and Wijiyanto. The company combines email, intranet, internal social media, WhatsApp, noticeboards, presentations, town hall meetings, direct discussion, and question-and-answer forums. Formal channels support consistency and documentation, while informal and two-way communication enable clarification and feedback. HR and managers act as communicators, interpreters, and facilitators. Participants nevertheless report incomplete explanations, technical language, delayed responses, and differing perceptions of policy relevance. Because the study provides no systematic measures of understanding, acceptance, participation, or welfare outcomes, it supports conclusions about communication practices and reported perceptions—not policy effectiveness or causal impact. Message consistency, audience-sensitive explanations, documented feedback, and accountable follow-up remain necessary.
Keywords: Corporate communication; Internal communication; Public policy; Communication strategy; TAPERA